The Role of Labor Induction in Racial Disparities in Cesarean Delivery - Wang, Xi (Mo Med, 2021)
We examined the interaction between race and labor induction in cesarean delivery in a cohort of 600,000 deliveries in the Cerner Health Facts database. Black women had higher likelihood cesarean (28.9 vs. 26.5%) and lower likelihood of induction of labor at delivery compared to white women (27.2 vs. 32.5%). Induction modified the association between race and cesarean—Black women (odds ratio=1.36, 95% confidence interval 1.30, 1.43) who were induced had significantly increased odds of cesarean delivery.